Pengembangan Lintasan Belajar Pada Pokok Bahasan Segiempat degan Menggunakan Pendekatan Pendidikan Matematika Realistik kelas VII di SMP Negeri 6 Padangsidimpuan - Ananti Pratiwi; Haddad Alwi Siregar (Neolectura, 2021)
This research is motivated by students lack understanding the concepts in the subject matter of a the rectangular for example, completing the area and circumference of the rectangular, because the material is presentad using the lecture method and only on certain materials using student discussion groups. The aim of the study was to determine validit, practicality and the trajectory design of the learning trajectory through a realistic mathematical education approach to the subject of rectangular at SMP N 6 Padangsidimpuan. This research is a design research with a type of validation study thet aims to develop local interaction theory (LIT) with collaboration between researches and educators to improve the quality of learning. This research was conducted at SMP N 6 Padangsidimpuan with trial subjects in class VII-2, totaling 31 students. The instrument of collecting data thet used is validation sheets, questionnaires, observations, and using validity and practical analysis techniques. The result of this study indicated thet the learning trajectory through a realistic mathematical education approach is said to be very valid and very practical. The vlidity of the learning trajectory is indicated by a value of 86,98% from analiyzing 3 validators. The practicality of the learning trajectory is shown by 82,71% of the student response questionnaire and observations. The learning trajectory produced in this study is in the form of activities carried out by students to achieve learning goals, where the purpose of the learning is to understanding of rectangular, types of rectangular, properties of rectangular, and circumference and area of rectangular.